A Novel Acoustic Uroflowmetry-Based Mobile App Voiding Diary: Comparison with Conventional Paper-Based Voiding Diary. (25th April 2022) - Kim, Jung Kwon; Kim, Hwanik; Ho, Jin-nyoung; Jeong, Seong Jin; Lee, Sangchul
Abstract : Objectives . To evaluate the usefulness of a novel acoustic uroflowmetry- (UFM-) based mobile application (app) voiding diary (VD) focusing on the (1) compliance and (2) correlation with a conventional paper-based VD. Materials and Methods . A total of 78 patients were included between December 2019 and June 2020, and a subsequent review of all data was performed. The analyzed data were as follows: (1) survey of convenience/satisfaction/preference comparing the two methods, (2) compliance regarding the completeness of both methods, and (3) correlation of each metric (24-hour urine volume, nocturnal urine volume, nocturnal polyuria index, total number of voids, number of daytime voids, number of nocturnal voids, and maximal bladder capacity) between the two methods. Results . The survey results of convenience, satisfaction, and preference were as follows. With regard to convenience and satisfaction area, higher scores are reported in the mobile app VD (mean ± standard deviation (SD); convenience: 7.47 ± 2.19 [app] vs. 4.20 ± 2.49 [paper]; satisfaction: 7.36 ± 2.17 [app] vs. 5.07 ± 2.65 [paper]). The median score of the overall preference for using the mobile app instead of the paper-based VD was 9 out of 10 (mean ± SD 7.82 ± 2.68 ). We also found a good correlation between the two methods for nocturnal urine volume (r = 0.55, p = 0.04 ), nocturnal polyuria index (r = 0.66, p = 0.23 ), total number of voids (r = 0.9, p = 0.02 ), number of nocturnal voids (r = 0.83, p = 0.02 ), and maximal bladder capacity (r = 0.89, p = 0.04 ). Conclusion . The acoustic UFM-based mobile app VD demonstrated favorable findings compared to the conventional paper-based VD.